Assessing restaurant operators responsiveness towards providing nutritional information on menu / Norrina Din, Mohd Salehuddin Mohd Zahari and Anida Ismail. - Din, Norrina; Mohd Zahari, Mohd Salehuddin; Ismail, Anida (2011)
The change in customer attitudes through educational knowledge has led to the increase in healthier eating including restaurant food and other foodservice operation. As nutritional information on the packaged, canned food and beverage products have been used for quite some time; full service and other types of restaurant operators sooner or later will be facing tremendous pressure from customers or probably the government in providing that information in the menu. This is evident when some of the established and world recognised fast food restaurants around the globe including Malaysia (even if only on selected nutrients) have started to make nutritional information available in their menu board owing to accusations of providing unhealthy food. Results of a recent study revealed there is an awakening of nutritional awareness among Malaysian restaurant customers. The majority of restaurant customers positively perceived the importance of providing nutritional information in the full service restaurant menu. These restaurants therefore should start to equip themselves with nutritional knowledge as they are most likely to be one of the targeted types of restaurants after the fast food restaurants despite some arguments that a restaurant is not about health but all about profit. This proposed study will investigate the willingness, constraints and obstacles of providing nutritional information of Malaysian full service restaurant operators. Qualitative approach through semi structured interview is considered to be the most suitable method for this proposed study. With that a structured interview will be designed in obtaining the relevant information from the informants. The full service restaurant operators in Penang will be only selected as a sample. The number of sufficient sampling will be later determined. Significant indicators are expected from this study particularly on the willingness of Malaysian full service restaurant operators in providing nutritional information and how sensitive they are with the changing of restaurant customer behaviour and the global restaurant trends as attaining customer needs leads to repeat patronization and in the long run contribute to restaurant business survival.